Pulmonary hypertension in pregnancy-the Anesthesiologist's perspective - A. McNeil; J. Chen; M.L. Meng (International Journal of Cardiology Congenital Heart Disease, 2021)
Modern treatment of pulmonary hypertension has reduced morbidity and mortality associated with this condition and has also improved the quality of life of women with pulmonary hypertension [1]. Pregnancy in women with pulmonary hypertension continues to present unique challenges. Pulmonary hypertension is classified as a modified World Health Organization class IV lesion and women with pulmonary hypertension are advised against pregnancy. Should pregnancy occur in a woman with pulmonary hypertension, and multi-disciplinary approach by the Pregnancy Heart Team is required for peripartum and postpartum care.